Investment incentives and the implementation of the Framework Convention on Tobacco Control: evidence from Zambia. Issue 4 (1st July 2015) - Lencucha, Raphael; Drope, Jeffrey; Labonte, Ronald; Zulu, Richard; Goma, Fastone
Abstract : Purpose: Policy misalignment across different sectors of government serves as one of the pivotal barriers to WHO Framework Convention on Tobacco Control (FCTC) implementation. This paper examines the logic used by government officials to justify investment incentives to increase tobacco processing and manufacturing in the context of FCTC implementation in Zambia. Methods: We conducted qualitative semistructured interviews with key informants from government, civil society and intergovernmental economic organisations (n=23). We supplemented the interview data with an analysis of public documents pertaining to the policy of economic development in Zambia. Results: We found gross misalignments between the policies of the economic sector and efforts to implement the provisions of the FCTC. Our interviews uncovered the rationale used by officials in the economic sector to justify providing economic incentives to bolster tobacco processing and manufacturing in Zambia: (1) tobacco is not consumed by Zambians/tobacco is an export commodity, (2) economic benefits outweigh health costs and (3) tobacco consumption is a personal choice. Conclusions: Much of the struggle Zambia has experienced in implementing the FCTC can be attributed to misalignments between the economic and health sectors. Zambia's development agenda seeks to bolster agricultural processing and manufacturing. Tobacco control proponents must recognise and work within this context in order to foster productive strategies with those working on tobacco supply issues. These findings are broadly applicable to the global context. It is important that the Ministry of Health monitors the tobacco policy of and engages with these sectors to find ways of harmonising FCTC implementation.